Comparison of Quetiapine Abuse and Misuse Reports to the FDA Adverse Event Reporting System With Other Second-Generation Antipsychotics - Kirk E Evoy; Chengwen Teng; Victor G Encarnacion; Brian Frescas; John Hakim; Stephen Saklad; Christopher R Frei (SAGE Publishing, 2019)
Background: Second-generation antipsychotics (SGAs) are assumed to have little abuse potential. However, reports of quetiapine abuse have emerged as prescribing has increased in recent years. The US Food and Drug Administration's (FDA) Adverse Event Reporting System (FAERS) provides postmarketing information regarding adverse drug events (ADEs). This is the first study to analyze quetiapine abuse-related ADEs reported to FAERS to determine whether a disproportionate rate of such events have been reported when compared with other commonly used SGAs. Methods: A cross-sectional analysis of FAERS data from January 1, 2015, to December 31, 2017, was performed. The total number of all-cause and abuse-related ADEs reported to FAERS regarding quetiapine, olanzapine, aripiprazole, and risperidone were identified, along with demographic and mortality data. The proportional reporting ratio (PRR) was calculated to assess disproportionate reporting of abuse-related adverse drug reactions between quetiapine and each of three alternative SGA medications. Results: Abuse-related ADEs represented 11% (3144/27 962) of total ADEs reported for quetiapine, 8% for olanzapine (1548/19 228), 5% (1380/29 699) for aripiprazole, and 3% (1168/45 518) for risperidone. The PRRs (95% confidence interval) for quetiapine versus olanzapine, aripiprazole, and risperidone were 1.40 (1.32-1.48), 2.42 (2.28-2.57), and 4.38 (4.10-4.68), respectively, indicating that abuse-related events were significantly more likely to be reported with quetiapine than each comparator drug. In addition, more deaths were reported among the abuse-related events regarding quetiapine (673) than olanzapine (200), aripiprazole (88), and risperidone (143). Conclusion: This study corroborates recent evidence indicating that quetiapine might possess a significantly higher abuse potential than other commonly used SGAs. Although prospective studies are needed to better understand the abuse potential of quetiapine, increased vigilance in monitoring for signs of substance abuse might be warranted when prescribing quetiapine.